Characteristics of highly cross‐linked polyethylene wear debris in vivo1. Issue 3 (22nd February 2013) - Baxter, Ryan M.; MacDonald, Daniel W.; Kurtz, Steven M.; Steinbeck, Marla J.
Abstract: Despite the widespread implementation of highly cross‐ linked polyethylene (HXLPE) liners to reduce the clinical incidence of osteolysis, it is not known if the improved wear resistance will outweigh the inflammatory potential of HXLPE wear debris generated in vivo . Thus, we asked: What are the differences in size, shape, number, and biological activity of polyethylene wear particles obtained from primary total hip arthroplasty revision surgery of conventional polyethylene (CPE) versus remelted or annealed HXLPE liners? Pseudocapsular tissue samples were collected from revision surgery of CPE and HXLPE (annealed and remelted) liners, and digested using nitric acid. The isolated polyethylene wear particles were evaluated using scanning electron microscopy. Tissues from both HXLPE cohorts contained an increased percentage of submicron particles compared to the CPE cohort. However, the total number of particles was lower for both HXLPE cohorts, as a result there was no significant difference in the volume fraction distribution and specific biological activity (SBA; the relative biological activity per unit volume) between cohorts. In contrast, based on the decreased size and number of HXLPE wear debris there was a significant decrease in total particle volume (mm 3 /g of tissue). Accordingly, when the SBA was normalized by total particle volume (mm 3 /gm tissue) or by component wear volume rate (mm 3 /year), functional biological activity of the HXLPE wear debris was significantly decreased compared to the CPE cohort. Indications for this study are that the osteolytic potential of wear debris generated by HXLPE liners in vivo is significantly reduced by improvements in polyethylene wear resistance. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 467–475, 2013.